Prevalence of anemia in older adults: A systematic and meta-analysis study - Aida Mohammadi; Mohsen Kazeminia; Alireza Chogan; Amir Jalali (Elsevier, 2024)
Background: Anemia in older adults is a natural consequence of aging and its symptoms and side effects are mostly neglected, which leads to negative effects on the quality of life in older adults. This study is an attempt to determine the prevalence of anemia in older adults through a systematic and meta-analysis study. Materials and Methods: This meta-analysis and systematic review was carried out in a time period from 1989 to 2022. To find articles pertinent to the topic of the study, Google Scholar, SID, MagIran, WoS, Scopus, and Embase databases were searched using keywords validated in MeSh/Emtree. Heterogeneity of studies was examined using the I2 index. Results: The search yielded 14,999 articles and eventually, 44 articles with a total sample size of 127,978 participants met the inclusion criteria of the study. The prevalence of anemia in older adults was estimated equal to 24.6 % (CI = 95 %; 19.1-31.1 %). The highest prevalence of anemia in older adults was in Africa (45.5 %; CI = 95 %; 3.9-94.5 %) and older adults living in nursing homes (53.7 %; CI = 95 %; 27.9-77.9 %). There was no significant difference between women and men in terms of the prevalence of anemia (P > 0.05). Conclusion: The findings indicated that the prevalence of anemia in older adults was high mostly in Africa. This finding requires more attention from experts, officials, and health policy makers.